Grip strength measurements at two different wrist extension positions in chronic lateral epicondylitis-comparison of involved vs. uninvolved side in athletes and non athletes: a case-control study - Bhargava Arti S; Eapen Charu; Kumar Senthil P (BMC, 2010)
Abstract Background Lateral epicondylitis is a common sports injury of the elbow caused due to altered muscle activation during repetitive wrist extension in many athletic and non-athletic endeavours. The amount of muscle activity and timing of contraction eventually is directly dependent upon joint position during the activity. The purpose of our study was to compare the grip strength in athletes with lateral epicondylalgia in two different wrist extension positions and compare them between involved and uninvolved sides of athletes and non-athletes. Methods An assessor-blinded case-control study of eight athletes and twenty-two non-athletes was done. The grip strength was measured using JAMAR® hand dynamometer in kilograms-force at 15 degrees (slightly extended) and 35 degrees (moderately extended) wrist extension positions (maintained by wrist splints) on both involved and uninvolved sides of athletes and non-athletes with unilateral lateral epicondylitis of atleast 3 months duration. Their pain was to be elicited with local tenderness and two of three tests being positive- Cozen's, Mill's manoeuvre, resisted middle finger extension tests. For comparisons of grip strength, Wilcoxon signed rank test was used for within-group comparison (between 15 and 35 degrees wrist extension positions) and Mann-Whitney U test was used for between-group (athletes vs. non-athletes) comparisons at 95% confidence interval and were done using SPSS 11.5 for Windows. Results Statistically significant greater grip strength was found in 15 degrees (27.75 ± 4.2 kgms in athletes; 16.45 ± 4.2 kgms in non-athletes) wrist extension than at 35 degrees (25.25 ± 3.53 kgm in athletes and 14.18 ± 3.53 kgm in non-athletes). The athletes had greater grip strength than non-athletes in each of test positions (11.3 kgm at 15 degrees and 11.07 kgm at 35 degrees) measured. There was also a significant difference between involved and uninvolved sides' grip strength at both wrist positions (4.44 ± .95 kgm at 15 degrees and 4.44 ± .86 kgm in 35 degrees) which was significant (p < .05) only in non-athletes. Conclusion The grip strength was greater in 15 degrees wrist extension position and this position could then be used in athletes with lateral epicondylalgia for grip strength assessment and designing wrist splint in this population.